Adoptive transfer of T regulatory cells inhibits lipopolysaccharide‐induced inflammation in fetal brain tissue in a late‐pregnancy preterm birth mouse model. (6th January 2017) - Wang, Fan; Xiao, Mi; Chen, Ru‐Juan; Lin, Xiao‐Jie; Siddiq, Muhammad; Liu, Li
Abstract: To evaluate the effect of regulatory T cells (Tregs) on the inflammation resulting from lipopolysaccharide (LPS) challenge in prenatal brain tissue, Tregs isolated from pregnant mice were transferred into model mice, and the expression levels of fork head family transcription factor (Foxp3), interleukin‐6 (IL‐6), CD68 (a marker of microglia), and toll‐like receptor 4 (TLR‐4) were assessed in the fetal brain tissue. Foxp3, IL‐6, and TLR‐4 expression were detected by polymerase chain reaction and Western blot; CD68 expression level was detected using immunochemical analysis. Foxp3, IL‐6, TLR‐4, and CD68 expressions in fetal brain were significantly induced by maternal LPS administration, and the increased expression levels were markedly reduced by adoptive transfer of Tregs. Maternal LPS exposure significantly induced inflammation in perinatal brain tissue, and Tregs negatively regulated this LPS‐induced inflammation.